Employee Retention Strategies for Generation Z in the Workforce - Mokoagow, Raditya; Permadi, Wisnu Kunto (Westscience Press, 2025)
Currently, the world of work is experiencing major changes in the demographic composition of its workforce. Generation Z, born between 1997 and 2012, is starting to enter the professional world and take on important roles in various sectors. The main objective of this research is to identify and map scientific publication trends related to employee retention strategies, especially those focused on Gen Z. The research method used in this article is a quantitative approach with bibliometric methods. This research aims to analyze trends and patterns of scientific publications related to the topic of employee engagement among Generation Z in the context of organizational work culture. It can be concluded that Generation Z employee retention strategies demand a more adaptive, personal and technology-based approach. Recent studies show that work flexibility, sustainable career development, and two-way communication are key factors in retaining young talent in the world of work. Policy makers in the field of human resources are advised to start designing data-driven HR policies that are able to capture Gen Z's work preferences and behavior more accurately